2021
DOI: 10.1002/jcla.24007
|View full text |Cite
|
Sign up to set email alerts
|

New prognostic factor for hepatitis B virus‐related decompensated cirrhosis: Ratio of monocytes to HDL‐cholesterol

Abstract: Hepatitis B virus (HBV) infection is an important health problem worldwide and HBV-infected patients can develop liver failure, liver cirrhosis, and hepatocellular carcinoma, resulting in an annual death toll of more than 1 million patients. 1,2 In China, HBV is the major cause of liver cirrhosis, and approximately 3% of HBV-infected patients with compensated cirrhosis develop decompensated cirrhosis (DeCi) each year, with a 5-year survival rate of only 15%. [3][4][5] Liver transplantation is an only reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Other studies reported significant elevation in liver disease patients as hepatitis B virus-related acute liver failure and hepatocellular carcinoma. 51 - 53 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported significant elevation in liver disease patients as hepatitis B virus-related acute liver failure and hepatocellular carcinoma. 51 - 53 …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that by improving the disturbance of hepatic cholesterol accumulation and KC polarization balance, we were able to reduce inflammatory injury and ultimately rescue the HBx-associated NASH phenotype, suggesting that the dysregulation of cholesterol homeostasis and MC polarization can be used as biomarkers of HBx-associated NASH immune injury. Reduced high-density lipoprotein cholesterol (HDL-C) and an elevated monocyte-to-HDL-C ratio (MHR) are significantly associated with mortality in HBV patients and can be used as prognostic biomarkers [ 46 , 47 ]. There is a complex association between the polarized phenotype of macrophages and HBV infection, with M1 activation indicating a strong immune response to HBV infection and M2 indicating persistent HBV infection, which is associated with disease progression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…An elevated monocyteto-HDL-C ratio has been shown to be predictive of increased mortality in HBV-related decompensated cirrhotic patients. 58 The potential mechanisms involve that the inflammation triggers monocyte release into the peripheral blood and produces pro-inflammatory molecules, leading to acceleration of inflammatory reactions and adverse outcomes. 59 Meanwhile, HDL-C serves as an anti-inflammatory lipoprotein by binding and neutralizing bac-terial lipopolysaccharides to facilitate their excretion.…”
Section: Hdl-related Biomarkers Predict Mortalitymentioning
confidence: 99%